OPEN GOVERNMENT: KEY ISSUES IN LATVIA - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This research aims to analyze key issues of open government in Latvia. A qualitative approach, the bibliometric analysis method, and the content analysis method were used in this research. Research data comes from the Scopus database, Web of Science, Semantic Scholar, Crossref, and Latvian government policy documents. This research has found 130 relevant articles, 4339 citations, 26 h-index, and 65 g-index, which shows that Latvian open government studies are of interest and have high impact and productivity. There are 1592 total link strengths, 524 occurrences, 180 topics, and 18 clusters in this study. Decision-making, public participation, government language, open data, information, government transparency, public administration, and communication are the topics that dominate. Meanwhile, current and potential research topics are public participation, civil dialogue, public information, wider participation, digital environment, promoting participation, youth participation, coordinational portal, organizing participation, and process participation. Currently, the Latvian government is focused on six of its 51 commitments. These commitments have great potential for creating a more open Latvia.